Factors associated with childhood overweight and obesity in Uganda: a national survey - Quraish Sserwanja; Linet M. Mutisya; Emmanuel Olal; Milton W. Musaba; David Mukunya (BMC, 2021)
Abstract Background Childhood obesity is an emerging public health problem globally. Although previously a problem of high-income countries, overweight and obesity is on the rise in low- and middle-income countries. This paper explores the factors associated with childhood obesity and overweight in Uganda using data from the Uganda Demographic and Health Survey (UDHS) of 2016. Methods We used Uganda Demographic and Health Survey (UDHS) 2016 data of 4338 children less than 5 years. Multistage stratified sampling was used to select study participants and data were collected using validated questionnaires. Overweight and obesity were combined as the primary outcome. Children whose BMI z score was over two were considered as overweight while those with a BMI z score greater than three were considered as obese. We used multivariable logistic regression to determine factors associated with obesity and overweight among children under 5 years of age in Uganda. Results The prevalence of overweight and obesity was 5.0% (217/4338) (95% CI: 4.3-5.6), with overweight at 3.9% (168/4338: 95% CI: 3.2-4.3) and obesity at 1.1% (49/4338: 95% CI: 0.8-1.5). Mother's nutritional status, sex of the child, and child's age were associated with childhood obesity and overweight. Boys were more likely to be overweight or obese (aOR = 1.81; 95% CI 1.24 to 2.64) compared to girls. Children who were younger (36 months and below) and those with mothers who were overweight or obese were more likely to have obesity or overweight compared to those aged 49-59 months and those with underweight mothers respectively. Children from the western region were more likely to be overweight or obese compared to those that were from the North. Conclusion The present study showed male sex, older age of the children, nutritional status of the mothers and region of residence were associated with obesity and overweight among children under 5 years of age.